Consideration of structural constraints in passive rotor blade design for improved performance - Lim, J.W. (My University, 2014)
This study applied parameterization to rotor blade designs for improved performance. In the design, parametric equations were used to represent blade planform changes over the existing rotor blade model. Design variables included blade twist, sweep, dihedral, and the radial control point. Updates to the blade structural properties with changes in the design variables allowed accurate evaluation of performance objectives and realistic structural constraints - blade stability, steady moments (flap bending, chord bending, and torsion), and the high g maneuver pitch link loads. Performance improvement was demonstrated with multiple parametric designs. Using a parametric design with the advanced airfoils, the predicted power reduction was 1.0% in hover, 10.0% at µ =0.30, and 17.0% at µ =0.40 relative to the baseline UH-60A rotor, but these were obtained with a 35% increase in the steady chord bending moment at µ =0.30 and a 20% increase in the half peak-to-peak pitch link load during the UH-60A UTTAS maneuver. Low vibration was maintained for this design. More rigorous design efforts, such as chord tapering and/or structural redesign of the blade cross section, would enlarge the feasible design space and likely provide significant performance improvement.